Low-loss temperature-stable celsian-based microwave dielectric ceramic material and preparation method thereof
Through a combination of precalcination and additive introduction, the in-situ synthesis of CaTiO3 is achieved and CuO is introduced during the ball milling process, which solves the problem of poor quality factor and temperature drift characteristics of existing graphite tailings barium feldspar-based microwave dielectric ceramic materials, and achieves high quality factor and good temperature drift characteristics to meet the needs of millimeter wave communication.
Patent Information
- Application Number
- CN202510422542.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-07
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2045-04-07
AI Technical Summary
The quality factor (Q×f value) of the existing graphite tailings barium feldspar-based microwave dielectric ceramic materials cannot meet the application requirements of millimeter wave communication, and the temperature drift characteristics are poor.
By combining precalcination of graphite tailing raw materials and introduction of additives, the solid phase reaction of Ca components in tailings and TiO2 is induced to achieve in situ synthesis of CaTiO3, and CuO is introduced during the ball milling process to eliminate the cationic defect of Ca.
The temperature drift and dielectric loss characteristics of barium feldspar-based ceramic materials have been improved. The resonant frequency temperature coefficient can be controlled within ±2ppm/℃, and the quality factor Q×f value exceeds 60,000GHz, meeting the practical application needs of millimeter wave communication devices.
Smart Images

Figure CN119912247A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to ceramics and a preparation method thereof, in particular to a low-loss temperature-stable celsium feldspar-based microwave dielectric ceramic material and a preparation method thereof. Background Art
[0002] With the rapid development of modern communication technology, especially the upgrading of mobile communication, satellite communication, military radar, and global positioning system (GPS), higher performance requirements are put forward for microwave devices. Microwave dielectric ceramics are characterized by their high dielectric constant (ε r )、High quality factor (Q), resonant frequency temperature coefficient (τ f ) and other excellent properties, which meet the requirements of miniaturization, integration, high reliability and low cost of microwave circuits. It is a key material for manufacturing microwave dielectric resonators and filters, and its related research is also increasingly valued.
[0003] The Chinese patent with application number 202110436475.5 introduces graphite tailings as raw materials into the microwave dielectric ceramic formula through the method of component compounding, which can form a single barium feldspar solid solution phase, and the loss characteristics are superior to those of calcium feldspar. However, the impurity components in the tailings will increase the dielectric loss of the ceramic material, making the quality factor (Q×f value) of the graphite tailing barium feldspar ceramic material unable to meet the application requirements of millimeter wave communication. Therefore, how to further improve the loss characteristics (Q) and temperature drift characteristics (τ f ) has become a key technical issue that needs to be solved urgently. Summary of the invention
[0004] Purpose of the invention: In order to overcome the deficiencies in the prior art, the purpose of the present invention is to provide a celsium feldspar-based microwave dielectric ceramic material with excellent dielectric properties. Another purpose of the present invention is to provide a convenient and controllable preparation method of a celsium feldspar-based microwave dielectric ceramic material that can reduce the sintering temperature.
[0005] Technical solution: The low-loss temperature-stable celsium feldspar-based microwave dielectric ceramic material described in the present invention is obtained by sintering the following raw materials in parts by weight: 265 to 272 parts of graphite tailings, 160 to 165 parts of BaCO3, 104 to 112 parts of Al2O3, 5 to 8 parts of TiO2, and 1 to 2 parts of CuO.
[0006] Furthermore, the main phase of the low-loss temperature-stable celsium feldspar-based microwave dielectric ceramic material is (Ba, Ca, Cu)Al2Si2O8, and the secondary phase is CaTiO3, wherein the mass percentage of the main phase is 93~95wt%, and the mass percentage of the secondary phase is 5~7wt%.
[0007] Furthermore, the relative dielectric constant of the low-loss temperature-stable celsium feldspar-based microwave dielectric ceramic material is 7.81~9.25, the quality factor is 45248~67351GHz, and the resonant frequency temperature coefficient is -2~2ppm / ℃.
[0008] The method for preparing the above-mentioned low-loss temperature-stable celsium feldspar-based microwave dielectric ceramic material comprises the following steps:
[0009] Step S1, crushing and grinding the graphite tailings, sieving, calcining at 700-800° C., and cooling to obtain graphite tailings powder;
[0010] Step S2, weighing graphite tailing powder and BaCO3, Al2O3, TiO2, La2O3, and CuO powders in proportion, and ball milling and mixing;
[0011] Step S3, drying the product obtained in step S2, calcining it, and cooling it in the furnace;
[0012] Step S4, ball-milling the powder obtained in step S3 for a second time and drying it;
[0013] Step S5, preparing a blank with the product obtained in step S4 and then sintering it to obtain a low-loss temperature-stable celsium feldspar-based microwave dielectric ceramic material.
[0014] Furthermore, in step S1, the particle size of the tailings powder after crushing, grinding and screening is 45-75 μm.
[0015] Furthermore, in step S1, the calcination temperature is 700-800°C, and the holding time is 0.5-1h. When the calcination temperature is lower than 700°C, the Ca-containing component in the ceramic material cannot be thermally decomposed into CaO, and then cannot react with the additive TiO2 to form CaTiO3 in step S2, resulting in performance degradation; when the sintering temperature is higher than 800°C, the Ca-containing component in the graphite tailing powder is completely thermally decomposed into CaO, and in step S2, CaO can completely react with the additive TiO2, thereby reducing the proportion of Ca element in the (Ba, Ca, Cu)Al2Si2O8 solid solution phase too much, resulting in performance degradation.
[0016] Furthermore, in step S2, BaCO3, Al2O3, TiO2, and CuO powders are all analytically pure, the ball milling is wet ball milling, the ball milling speed is 250-300 r / min, and the ball milling time is 8-12 h.
[0017] Furthermore, in step S3, the calcination temperature is 950-1050°C and the holding time is 2-4h. If the calcination temperature is lower than 950°C, the powder contains the raw material phase, and the impurity phase is likely to appear in the subsequent sintering process; if the calcination temperature is higher than 1050°C, the powder particle size becomes larger, and the reaction activity becomes worse in the subsequent sintering process.
[0018] Furthermore, in step S4, the ball milling is wet ball milling, the ball milling speed is 200-250 r / min, and the ball milling time is 4-6 h.
[0019] Furthermore, in step S5, the sintering temperature is 1150-1250°C, and the temperature is kept for 3-5 hours after sintering, and then cooled with the furnace. If the sintering temperature is lower than 1150°C, the sintering power of the ceramic material is insufficient, the density is reduced, and the performance is reduced; if the sintering temperature is higher than 1250°C, the ceramic grains grow abnormally, and the grains are coated during the grain growth process, resulting in an increase in porosity, a decrease in density, and a decrease in performance.
[0020] Preparation principle: Graphite tailings are pre-calcined to ensure that part of the Ca component in the tailings is thermally decomposed into CaO. In the subsequent ball milling and calcination steps, it is evenly mixed with the additive TiO2 and the CaTiO3 second phase is synthesized in situ. Since CaTiO3 is a common positive temperature drift compensator (~ +800ppm o / C), the introduction of the second phase improves the graphite tailing microwave dielectric ceramic material with negative resonant frequency temperature coefficient. In addition, the introduction of a small amount of CuO in the first ball milling can eliminate the Ca cation defects caused by the synthesis of the CaTiO3 phase, occupy the Ca lattice site in the form of ion replacement, and improve the sintering characteristics and loss characteristics of the ceramic material.
[0021] Beneficial effects: Compared with the prior art, the present invention has the following significant features:
[0022] 1. By combining the pre-calcination of graphite tailings raw materials with the introduction of additives, the solid-phase reaction between the Ca component in the tailings and TiO2 is induced, and the in-situ synthesis of the CaTiO3 performance-enhancing phase is achieved, which improves the temperature drift characteristics of celsium feldspar-based ceramic materials. The resonant frequency temperature coefficient can be controlled within ±2ppm / ℃, which comprehensively improves the microwave dielectric properties of ceramic materials to meet the actual application requirements of millimeter-wave communication devices;
[0023] 2. The introduction of CuO in the first ball milling process can eliminate the Ca cation defects caused by the synthesis of CaTiO3 phase, occupy the Ca lattice site by ion replacement, and improve the sintering characteristics and dielectric loss characteristics of celsium feldspar-based ceramic materials. The sintering temperature is reduced to 1150℃, and the quality factor Q×f value can exceed 60000GHz. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is the XRD pattern of the low-loss temperature-stable celsium feldspar-based microwave dielectric ceramic material obtained in Example 2 of the present invention;
[0025] Figure 2 This is an XRD graph of the low-loss temperature-stable celsium feldspar-based microwave dielectric ceramic material obtained in Comparative Example 1;
[0026] Figure 3 This is a SEM image of the low-loss temperature-stable celsium feldspar-based microwave dielectric ceramic material obtained in Example 2 of the present invention;
[0027] Figure 4 This is a SEM image of the low-loss temperature-stable celsium feldspar-based microwave dielectric ceramic material obtained in Example 2. DETAILED DESCRIPTION
[0028] The materials, reagents, instruments, etc. used in the following examples are all commercially available unless otherwise specified. The experimental methods without specific conditions in the examples are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The specific composition of graphite tailings is shown in Table 1.
[0029] Table 1 Chemical composition of graphite tailings
[0030]
[0031] Example 1
[0032] A method for preparing a low-loss temperature-stable celsium feldspar-based microwave dielectric ceramic material comprises the following steps:
[0033] Step S1, crushing and grinding the graphite tailings respectively, and sieving them to make the average particle size of the graphite tailings powder be 45 μm. Place the crucible containing the graphite tailings powder in a high-temperature muffle furnace for calcination at 700° C., keep the temperature for 0.5 h, and then cool naturally.
[0034] Step S2, weigh 26.5 g of graphite tailings powder, 16.0 g of BaCO3 powder, 10.4 g of Al2O3 powder, 0.8 g of TiO2 powder, and 0.1 g of CuO powder, mix the five powders, and wet-mill at a speed of 250 r / min for 8 h.
[0035] Step S3, drying the product obtained in step S2, placing it in a muffle furnace for calcination at 950° C. and keeping it at this temperature for 2 hours, and cooling it with the furnace.
[0036] Step S4: The calcined powder is subjected to secondary ball milling, wet ball milling at a rotation speed of 200 r / min for 4 h, and then dried.
[0037] Step S5, taking out the powder obtained in step S5, pressing the green body and placing it in a high-temperature muffle furnace for sintering, the sintering temperature is 1250° C., the heat preservation time is 3 hours, and then cooling with the furnace, finally obtaining a low-loss temperature-stable celsium feldspar-based microwave dielectric ceramic material.
[0038] The phase contents of the low-loss temperature-stable celsium feldspar-based microwave dielectric ceramic material obtained in this embodiment (by mass ratio) are as follows: (Ba, Ca, Cu)Al2Si2O8 accounts for 93.0%, and CaTiO3 accounts for 7.0%.
[0039] Example 2
[0040] A method for preparing a low-loss temperature-stable celsium feldspar-based microwave dielectric ceramic material comprises the following steps:
[0041] Step S1, crushing and grinding the graphite tailings respectively, and sieving them to make the average particle size of the graphite tailings powder be 50 μm. Place the crucible containing the graphite tailings powder in a high-temperature muffle furnace for calcination at 750° C., keep the temperature for 1 hour, and then cool naturally.
[0042] Step S2, weigh 26.7 g of graphite tailings powder, 16.1 g of BaCO3 powder, 10.6 g of Al2O3 powder, 0.7 g of TiO2 powder, and 0.12 g of CuO powder, mix the five powders, and wet-mill at a rotation speed of 275 r / min for 10 h.
[0043] Step S3, drying the product obtained in step S2, placing it in a muffle furnace for calcination at 1000° C. and keeping it warm for 3 hours, and cooling it with the furnace.
[0044] Step S4, ball milling the calcined powder for a second time, wet ball milling at a speed of 250 r / min for 5 h, and drying.
[0045] Step S5, taking out the powder obtained in step S5, pressing the green body and placing it in a high-temperature muffle furnace for sintering, the sintering temperature is 1150° C., the holding time is 4 hours, and then cooling with the furnace, finally obtaining a low-loss temperature-stable celsium feldspar-based microwave dielectric ceramic material.
[0046] The phase contents of the low-loss temperature-stable celsium feldspar-based microwave dielectric ceramic material obtained in this embodiment (by mass ratio) are as follows: (Ba, Ca, Cu)Al2Si2O8 accounts for 93.5%, and CaTiO3 accounts for 6.5%.
[0047] Example 3
[0048] A method for preparing a low-loss temperature-stable celsium feldspar-based microwave dielectric ceramic material comprises the following steps:
[0049] Step S1, crushing and grinding the graphite tailings respectively, and sieving them to make the average particle size of the graphite tailings powder be 60 μm. Place the crucible containing the graphite tailings powder in a high-temperature muffle furnace for calcination at 800° C., keep the temperature for 0.5 h, and then cool naturally.
[0050] Step S2, weigh 26.9 g of graphite tailings powder, 16.2 g of BaCO3 powder, 10.8 g of Al2O3 powder, 0.6 g of TiO2 powder, and 0.14 g of CuO powder, mix the five powders, and wet-mill at a rotation speed of 300 r / min for 11 h.
[0051] Step S3, drying the product obtained in step S2, placing it in a muffle furnace for calcination at 1025° C. and keeping it at this temperature for 4 hours, and cooling it with the furnace.
[0052] Step S4: ball mill the calcined powder for a second time, wet ball mill at a speed of 225 r / min for 6 h, and dry.
[0053] Step S5, taking out the powder obtained in step S5, pressing the green body and placing it in a high-temperature muffle furnace for sintering, the sintering temperature is 1250° C., the heat preservation time is 4 hours, and then cooling with the furnace, finally obtaining a low-loss temperature-stable celsium feldspar-based microwave dielectric ceramic material.
[0054] The phase contents of the low-loss temperature-stable celsium feldspar-based microwave dielectric ceramic material obtained in this embodiment (by mass ratio) are as follows: (Ba, Ca, Cu)Al2Si2O8 accounts for 94.0%, and CaTiO3 accounts for 6.0%.
[0055] Example 4
[0056] A method for preparing a low-loss temperature-stable celsium feldspar-based microwave dielectric ceramic material comprises the following steps:
[0057] Step S1, the graphite tailings are crushed, ground and sieved respectively to make the average particle size of the graphite tailings powder be 70 μm. The crucible containing the graphite tailings powder is placed in a high-temperature muffle furnace for calcination at 750° C., kept at this temperature for 1 hour, and then cooled naturally.
[0058] Step S2: weigh 27.1 g of graphite tailings powder, 16.4 g of BaCO3 powder, 11.0 g of Al2O3 powder, 0.55 g of TiO2 powder, and 0.18 g of CuO powder, mix the five powders, and wet-mill at a rotation speed of 300 r / min for 12 h.
[0059] Step S3, drying the product obtained in step S2, placing it in a muffle furnace for calcination at 975°C and keeping it at this temperature for 4 hours, and cooling it with the furnace.
[0060] Step S4, ball milling the calcined powder for a second time, wet ball milling at a speed of 200 r / min for 5 h, and drying.
[0061] Step S5, taking out the powder obtained in step S5, pressing the green body and placing it in a high-temperature muffle furnace for sintering, the sintering temperature is 1200° C., the heat preservation time is 5 hours, and then cooling with the furnace, finally obtaining a low-loss temperature-stable celsium feldspar-based microwave dielectric ceramic material.
[0062] The phase contents of the low-loss temperature-stable celsium feldspar-based microwave dielectric ceramic material obtained in this embodiment (by mass ratio) are as follows: (Ba, Ca, Cu)Al2Si2O8 accounts for 94.5%, and CaTiO3 accounts for 5.5%.
[0063] Example 5
[0064] A method for preparing a low-loss temperature-stable celsium feldspar-based microwave dielectric ceramic material comprises the following steps:
[0065] Step S1, crushing and grinding the graphite tailings respectively, and sieving them to make the average particle size of the graphite tailings powder be 75 μm. Place the crucible containing the graphite tailings powder in a high-temperature muffle furnace for calcination at 700° C., keep the temperature for 0.5 h, and then cool naturally.
[0066] Step S2, weigh 27.2 g of graphite tailings powder, 16.5 g of BaCO3 powder, 11.2 g of Al2O3 powder, 0.5 g of TiO2 powder, and 0.2 g of CuO powder, mix the five powders, and wet-mill at a rotation speed of 275 r / min for 9 h.
[0067] Step S3, drying the product obtained in step S2, placing it in a muffle furnace for calcination at 1050° C. and keeping it at this temperature for 3 hours, and cooling it with the furnace.
[0068] Step S4: ball mill the calcined powder for a second time, wet ball mill at a speed of 225 r / min for 4 h, and dry.
[0069] Step S5, taking out the powder obtained in step S5, pressing the green body and placing it in a high-temperature muffle furnace for sintering, the sintering temperature is 1200° C., the heat preservation time is 5 hours, and then cooling with the furnace, finally obtaining a low-loss temperature-stable celsium feldspar-based microwave dielectric ceramic material.
[0070] The phase contents of the low-loss temperature-stable celsium feldspar-based microwave dielectric ceramic material obtained in this embodiment (by mass ratio) are as follows: (Ba, Ca, Cu)Al2Si2O8 accounts for 95.0%, and CaTiO3 accounts for 5.0%.
[0071] Comparative Example 1
[0072] The graphite tailings were crushed, ground and sieved separately to make the average particle size of the graphite tailings powder 50μm. The crucible containing the graphite tailings powder was placed in a high-temperature muffle furnace for calcination at 750℃, kept warm for 1h, and then cooled naturally. Weigh 26.7g of graphite tailings powder, 16.1g of BaCO3 powder, 10.6g of Al2O3 powder, and 0.12g of CuO powder, mix the four powders, and wet-mill at a speed of 275r / min for 10h. The ball-milled and dried powder was placed in a muffle furnace for calcination at 1000℃ and kept warm for 3h, and cooled with the furnace. The calcined powder was ball-milled for the second time at a speed of 250 r / min for 5 h. The dried powder was pressed into a green compact and sintered in a high-temperature muffle furnace at a sintering temperature of 1150°C for 4 h. The powder was then cooled in the furnace to obtain a microwave dielectric ceramic material. The phase content of the ceramic material (by mass ratio) is: (Ba, Ca, Cu)Al2Si2O8 accounts for 100%.
[0073] Comparative Example 2
[0074] The graphite tailings were crushed, ground and sieved separately to make the average particle size of the graphite tailings powder 50μm. The crucible containing the graphite tailings powder was placed in a high-temperature muffle furnace for calcination at 750℃, kept warm for 1h, and then cooled naturally. Weigh 26.7g of graphite tailings powder, 16.1g of BaCO3 powder, 10.6g of Al2O3 powder, and 0.7g of TiO2 powder, mix the four powders, and wet-mill at a speed of 275r / min for 10h. The ball-milled and dried powder was placed in a muffle furnace for calcination at 1000℃ and kept warm for 3h, and cooled with the furnace. The calcined powder was placed in a ball mill and wet-milled at a speed of 250r / min for 5 hours. The dried powder was pressed into a green compact and sintered in a high-temperature muffle furnace at a sintering temperature of 1150°C for 4 hours. The powder was then cooled in the furnace to obtain a microwave dielectric ceramic material. The phase content of the ceramic material (by mass ratio) is as follows: (Ba, Ca)Al2Si2O8 accounts for 93.4% and CaTiO3 accounts for 6.6%.
[0075] Comparative Example 3
[0076] The graphite tailings were crushed, ground and sieved separately to make the average particle size of the graphite tailings powder 50μm. Weigh 26.7g of graphite tailings powder, 16.1g of BaCO3 powder, 10.6g of Al2O3 powder, 0.7g of TiO2 powder, and 0.12g of CuO powder, mix the five powders, and wet-mill them at a speed of 275r / min for 10h. The dried powder after ball milling was placed in a muffle furnace for calcination at 1000℃ and kept warm for 3h, and then cooled with the furnace. The calcined powder was ball milled for a second time, wet-milled at a speed of 250r / min for 5h, and the dried powder was pressed and sintered in a high-temperature muffle furnace. The sintering temperature was 1150℃, the insulation time was 4h, and then cooled with the furnace to obtain a microwave dielectric ceramic material. The phase content of the ceramic material (by mass ratio): (Ba, Ca, Cu)Al2Si2O8 accounted for 100%.
[0077] Table 2 shows the microwave dielectric properties and sintering properties of the microwave dielectric ceramic materials obtained under different formulations and process conditions for Examples 1-5 and Comparative Examples 1-3. Among them, the ceramic sample prepared in Example 2 has the highest quality factor, a near-zero resonant frequency temperature coefficient, and the lowest sintering temperature, and is the optimal embodiment. Figure 1 As shown in FIG. 1 , the main phase is (Ba, Ca, Cu)Al2Si2O8 and the secondary phase is CaTiO3. Comparative Example 1 prepared a ceramic sample without adding TiO2. Figure 2 As shown, the phase composition of the ceramic sample is (Ba, Ca, Cu)Al2Si2O8. Compared with Example 2, due to the lack of CaTiO3 reinforcement phase, the τf The absolute value is high, and the Q×f value is also low. In Comparative Example 2, a ceramic sample without CuO addition was prepared, which is different from Example 2 (microscopic morphology as shown in Figure 3 Compared with the 2+ Filling cations and occupying Ca sites, the Q×f value of the sample decreases significantly, and the sintering density also decreases, and a large number of pores appear, such as Figure 4 In Comparative Example 3, the graphite tailings powder was not pre-calcined, and the Ca component in the tailings raw material could not exist in the form of CaO, and could not synthesize the CaTiO3 reinforcement phase with the TiO2 additive during the high-temperature calcination process, which made the τ f The absolute value is high, and the Q×f value is also low.
[0078] Table 2 Properties of materials obtained from Examples 1-5 and Comparative Examples 1-3
[0079]
Claims
1. A low-loss temperature-stable celsium feldspar-based microwave dielectric ceramic material, characterized in that: It is prepared by sintering the following raw materials in parts by weight: 265-272 parts of graphite tailings, 160-165 parts of BaCO3, 104-112 parts of Al2O3, 5-8 parts of TiO2, and 1-2 parts of CuO.
2. The low-loss temperature-stable celsium feldspar-based microwave dielectric ceramic material according to claim 1, characterized in that: Its master The physical phase is (Ba, Ca, Cu)Al2Si2O8, and the secondary physical phase is CaTiO3, wherein the mass percentage of the main physical phase is 93~95wt%, and the mass percentage of the secondary physical phase is 5~7wt%.
3. The low-loss temperature-stable celsium feldspar-based microwave dielectric ceramic material according to claim 1, characterized in that: Its relative dielectric constant is 7.81~9.25, the quality factor is 45248~67351GHz, and the resonant frequency temperature coefficient is -2.0~2.0ppm / ℃.
4. A method for preparing a low-loss temperature-stable celsium feldspar-based microwave dielectric ceramic material according to any one of claims 1 to 3, characterized in that: The following steps are involved: Step S1, crushing and grinding the graphite tailings, sieving, calcining at 700-800° C., and cooling to obtain graphite tailings powder; Step S2, weighing graphite tailing powder and BaCO3, Al2O3, TiO2, La2O3, and CuO powders in proportion, and ball milling and mixing; Step S3, drying the product obtained in step S2, calcining it, and cooling it in the furnace; Step S4, ball-milling the powder obtained in step S3 for a second time and drying it; Step S5, preparing a blank with the product obtained in step S4 and then sintering it to obtain a low-loss temperature-stable celsium feldspar-based microwave dielectric ceramic material.
5. The method for preparing the low-loss temperature-stable celsium feldspar-based microwave dielectric ceramic material according to claim 4, characterized in that: In the step S1, the particle size of the graphite tailings powder is 45-75 μm.
6. The method for preparing the low-loss temperature-stable celsium feldspar-based microwave dielectric ceramic material according to claim 4, characterized in that: In the step S1, the calcination is followed by heat preservation for 0.5 to 1 hour.
7. The method for preparing the low-loss temperature-stable celsium feldspar-based microwave dielectric ceramic material according to claim 4, characterized in that: In the step S2, the BaCO3, Al2O3, TiO2 and CuO powders are all analytically pure, the ball milling is wet ball milling, the ball milling speed is 250-300 r / min, and the ball milling time is 8-12 h.
8. The method for preparing the low-loss temperature-stable celsium feldspar-based microwave dielectric ceramic material according to claim 4, characterized in that: In step S3, the calcination temperature is 950-1050° C., and the holding time is 2-4 hours.
9. The method for preparing the low-loss temperature-stable celsium feldspar-based microwave dielectric ceramic material according to claim 4, characterized in that: In step S4, the ball milling is wet ball milling, the ball milling speed is 200-250 r / min, and the ball milling time is 4-6 h.
10. The method for preparing the low-loss temperature-stable celsium feldspar-based microwave dielectric ceramic material according to claim 4, characterized in that: In the step S5, the sintering temperature is 1150-1250° C., and the sintering temperature is kept for 3-5 hours, followed by cooling with the furnace.
Citation Information
Patent Citations
Sintered ceramic body, manufacturing method thereof, and ceramic structure
CN102060516A
Monoclinic phase-based low-dielectric microwave dielectric ceramic material and preparation method thereof
CN111635222A
Graphite tailing-based microwave dielectric ceramic material and preparation method thereof
CN113121214A
Low-cost nonmetal mineral microwave dielectric ceramic material and preparation method thereof
CN115959893A
Ceramic material and method of forming the same
US20240217878A1
Cited By
Monoclinic Ba1-xCaxAl2Si2O8 ceramic material and preparation method thereof
CN119080487A
Monoclinic Ba1-xCaxAl2Si2O8 porous ceramic material and preparation method thereof
CN121405498A